Improving the thermal efficiency of a car wax oven using CFD simulation and measurement. (3rd April 2019) - Nazif, Hamid Reza
Abstract: Computational fluid dynamics (CFD) and experimental measurements are used for simulating the heat-up cabin of a car wax oven. Considering the turbulent flow behavior, the realizable k-ε model that is suitable for flow with severe strain and stress rate is adopted. No notable fluid flow was reported during the stable oven condition at the interface of heat-up and the next cabins. It makes it possible to solely simulate the heat-up cabin and offers significant saving in computational expenses. To apply boundary conditions, grid matrices are used, and the mean air velocity and temperature are estimated across the inlets and outlets. Furthermore, the measured data at the nozzles are compared with the simulation results. The results of the simulation give close prediction of the measured data. It is shown that the oven energy efficiency is significantly improved by making three small variations on the oven geometry, based on primary simulation results. Reducing supply and return air pressure loss tend to lead to better air flow circulation and consequently, a 25% increase in the measured mean car body temperature.